De la musique pour le peuple: une proposition d’analyse des premiers disques folkloriques du Chant du Monde - Thomas, Jonathan (Analitica. Rivista online di studi musicali, 2017)
Between 1936 and 1938, France was governed by the Front populaire, a coalition of left-wing parties that constitutes one of the strongest symbols of hope and social justice in recent French history. During the Front populaire’s administration, a series of social and economic measures were developed in order to free workers’ time and allow them holidays and leisure activities. Cinema, radio, theatre and music emerged as powerful tools of popular education. Within this context, Le Chant du Monde – a record company founded in 1937 under the influence of the French Communist Party – released a series of discs dedicated to French folk song repertoire. Arranged by some famous contemporary composers (such as Charles Koechlin, Georges Auric or Darius Milhaud), these folk songs were used to represent French history in accordance with left-wing social and political values. These records could also help to support the national character and the legitimacy of the Front populaire’s government. This article considers the practice of music analysis as a means to investigate the relation between music and politics. More precisely, by drawing on the analysis of different songs and arrangements published by Le Chant du Monde as well as on the examination of some composers’ writings, it will explore the political dimension of musical records, conceived as a tool of popular education and political legitimation.